Patients' stories of encounters with doctors: Expectations and anxieties - Daniella Arieli; Batya Tamir (The Beryl Institute, 2018)
The study contributes to the understanding of how patients experience encounters with doctors. The study is based on the gathering and analysis of subjective stories of 'healthy' patients who live in Israel about their encounters with doctors. On the one hand, medical encounters were described as functional ritualistic events, and the doctor was described as an indifferent clerk. On the other hand, and often at the same time, medical encounters were perceived as incredibly meaningful and potentially fateful events, and the doctor as a supreme authority. Four main inter-connected expressions of this were: 1. The encounter as a ritual: A convenient but alarming arrangement; 2. Alone in the struggle to feel well: The unspoken anxiety; 3. Time concerns; 4. Paying for reassurance- Turning to physicians in private practice. The research indicated that the visit to the doctor often raises "healthy" patients' confrontation with existential fears, and that they expect the doctor to be sensitive to their anxieties, and reassuring. Alas, these emotions and expectations often remain unspoken. There is a need for further discussion regarding the different ways patients and doctors perceive medical encounters. Acknowledging potential gaps in meanings and expectations and addressing their implications on patients' experiences is crucial for patients; doctors and policy makers.